Preseganje ovir pri vzpostavljanju izposoje (in prodaje) e-knjig v Sloveniji - Zamida, Renata (Šolska knjižnica, 2012)
The author focuses on the issue of e-book lending in libraries finishing with a suggestion for lending of e-books in Slovenian libraries which could use successful foreign models as an example. The emergence of e-books causes ever greater user demand in Slovenian libraries. The publishers have already taken the first careful steps, because some Slovenian publishers already offer their e-books. Slovenian library network holds an exceptionally important position in Slovenian cultural space, however, this position is changing with the emergence of new forms of book and new distribution paths. The option of e-book lending presented a new milestone in the offer of Slovenian libraries and an enhanced user experience for their readers. Reading on e-readers, tablet computers and mobile telephones is already present in Slovenia, however it is still a fresh and exciting area waiting for the next step.
Keywords: e-bralniki; e-knjige; izposoja; knjižnice; poslovni modeli; Slovenija; založbe; založništvo